Hiding Existence of Communication Using Image Steganography - Nimje, Swati; Belkhede, Amruta; Chaudhari, Gaurav; Pawar, Akanksha; Kharbikar, Kunali (International Journal of Computer Sciences and Engineering, 2014)
Now a day, maintaining the security of the secret information has been a great challenge. Sending message habitually through a communication channel like internet draws the attention of third parties and hackers, perhaps causing attempts to break and expose the sent messages. Some solutions to be discussed is how to pass information in manner that the very existence of the message is unknown in order to repel attention of the potential attacker. Besides hiding data for secret communication, an approach of information hiding can be extended to copyright protection for digital media. In this paper, we propose modified LSB technique for Image Steganography to hide secret message i.e. Text, Image, Audio and Video in an Image which makes it harder for unauthorised people to extract the original message.